2010
DOI: 10.1089/ten.tec.2009.0648
|View full text |Cite
|
Sign up to set email alerts
|

Nonviral Transfection Strategies for Keratinocytes, Fibroblasts, and Endothelial Progenitor Cells for Ex Vivo Gene Transfer to Skin Wounds

Abstract: In a search for the optimal nonviral gene transfer technique in epidermal and dermal supportive extracellular matrix studies, we investigated the efficiency of late generation liposomal transfection reagents and nucleofection of fibroblasts (FBs), endothelial progenitor cells (EPCs), and keratinocytes (KCs) as essential indicators of healing skin wounds. FBs, KCs, and EPCs were grown under serum-reduced conditions and manipulated according to optimized in vitro manufacturer protocols. Fugene HD, Effectene, PEI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…To evaluate the potential for targeted gene suppression by siRNA-based SNA-NCs through noninvasive topical delivery, we first investigated their uptake in primary normal human keratinocytes (hKCs), which are typically difficult to transfect (25). hKCs were incubated with Cy3 fluorophore-labeled SNA-NCs (Table S1), and entry was studied by confocal fluorescence microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the potential for targeted gene suppression by siRNA-based SNA-NCs through noninvasive topical delivery, we first investigated their uptake in primary normal human keratinocytes (hKCs), which are typically difficult to transfect (25). hKCs were incubated with Cy3 fluorophore-labeled SNA-NCs (Table S1), and entry was studied by confocal fluorescence microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…However, as most patients with PG and other skin conditions already use multiple topical and systemic treatments to control the painful lesions, the impact of this is likely to be reduced. In addition, wound healing is a complex process involving many interacting cell types and growth factors, which is time limited, and therefore transgene expression which is only temporary is not unfavourable [54]. PG is a non-malignant disease, so a transfection rate of 100% is not required; the relatively low transfection efficiency of liposomes [15] is not necessarily problematic.…”
Section: Discussionmentioning
confidence: 99%
“…Complexes of nTMag particles associated with pDNA under an oscillating magnetic field with a frequency of 2 Hz yielded 25% transgene-expressing cells compared with 22% with Lipofectamine 2000 (8). The best reported results for the transfection of porcine primary fibroblasts have been achieved with optimized nucleofection protocols (6,(23)(24)(25). Richter et al (25) reported a rate of 53% eGFP-positive PFF cells with low cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%